The Level of Possession of Tenth Grade Students of Nablus of Mathematical Generalization - Mayada Sammar (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
The study aims to reveal the level of possession of tenth grade students in the city of Nablus in Palestine of mathematical generalization, based on gender, general academic achievement, tendency towards learning mathematics, and type of school (public and private). The study population included all tenth grade students in the city of Nablus. The sample consisted of (315) male and female students. The researcher used a descriptive method, and the sample was chosen by a satratified random method to control for gender. Data were collected using a mathematical generalization test. The results of the study showed that the students' level of mathematical generalization was low, especially in the field of algebra and geometry. In the areas of numbers and measurement, the students' level was average. The general academic achievement variables, the tendency towards learning mathematics, and the type of school affected the ability to generalize mathematics in favor of high-achieving students who tend to learn mathematics and of private school students. The study recommends encouraging teachers to use appropriate teaching methods related to mathematical generalization, especially in the subjects of algebra and geometry.